Policy Making in Newborn Screening Needs a Structured and Transparent Approach - Jansen, Marleen E.; Lister, Karla J.; van Kranen, Henk J.; Cornel, Martina C. (Frontiers in Public Health, 2017)
Purpose Newborn bloodspot screening (NBS) programs have expanded significantly in the past years and are expected to expand further with the emergence of genetic technologies. Historically, NBS expansion has often occurred following ad hoc consideration of conditions, instead of a structured and transparent approach. In this review, we explore issues pertinent to NBS policy making, through the lens of the policy cycle: (a) agenda setting, (b) policy advice, (c) policy decision, (d) implementation, and (e) evaluation. Methods A literature search was conducted to gather information on the elements specific to NBS and its policy making process. Results The review highlighted two approaches to nominate a condition: a structured approach through horizon scanning; and an ad hoc process. For assessment of a condition, there was unanimous support for a robust process based on criteria. While the need to assess harms and benefits was a repeated theme in the articles, there is no agreed-upon threshold for benefit in decision-making. Furthermore, the literature was consistent in its recommendation for an overarching, independent, multidisciplinary group providing recommendations to government. An implementation plan focusing on the different levels on which NBS operates and the information needed on each level is essential for successful implementation. Continuously monitoring, and improving a program is vital, particularly following the implementation of screening for a new condition. An advisory committee could advise on implementation, development, review, modification, and cessation of (parts of) NBS. Conclusion The results highlight that there are a wave of issues facing NBS programs that policy makers must take into account when developing policy processes. What conditions to screen, and the technologies used in NBS, are both up for debate.